2007
DOI: 10.1108/02634500710834160
|View full text |Cite
|
Sign up to set email alerts
|

Surf tribal behaviour: a sports marketing application

Abstract: Purpose -The purpose of this paper is to investigate "tribal" consumption behaviour and its relationship to branding, in the particular context of the surfing community in Portugal. Design/methodology/approach -Two focus group meetings with "surfers" and "fans" respectively, in April 2006, were enriched by computerised projective techniques and program-assisted design (PAD) technology, backed by high quality video prompts. Qualitative data analysis was enhanced by quantified data collected in the PAD phase. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…However, although numerous prior studies demonstrate how consumers use brands to communicate the type of person they are to others (e.g. Belk, 1988;Moutinho et al, 2007;O'Cass, 2000), there is a dearth of research investigating whether the desire for self-expressive brands may serve as a motivation to spread WOM (Saenger et al, 2013). A study of brand love has suggested a positive relationship between self-expressive brands and WOM (Carroll and Ahuvia, 2006), but this relationship has remained largely unexplored in the academic literature.…”
Section: H7: There Is a Positive Relationship Between Brand Tribalismmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although numerous prior studies demonstrate how consumers use brands to communicate the type of person they are to others (e.g. Belk, 1988;Moutinho et al, 2007;O'Cass, 2000), there is a dearth of research investigating whether the desire for self-expressive brands may serve as a motivation to spread WOM (Saenger et al, 2013). A study of brand love has suggested a positive relationship between self-expressive brands and WOM (Carroll and Ahuvia, 2006), but this relationship has remained largely unexplored in the academic literature.…”
Section: H7: There Is a Positive Relationship Between Brand Tribalismmentioning
confidence: 99%
“…In this paper, we contend that, in the act of consuming or wearing certain brands, tribes can express their shared passion, and the wearing of fashion becomes a demonstration of tribal values. In this way, consumers can create a social link that allows tribal members to signal their shared passion, and gain acceptance from the tribe (Cova 1997;Mitchell and Imrie, 2011;Moutinho et al, 2007). This study considers that using the brand to express one's self-concept, may form part of the signaling ritual of the brand tribe.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such organizations thus become subject to "the spectacle" (Debord 1967), with image becoming as relevant as substance (Alvesson 1990): to be seen to be green, for example, becomes an end in itself, irrespective of the substance of the claims being made. As the post-modern consumer behaviour researchers argue, image is a selling entity which the product tries to represent (Moutinho et al 2007). It is not the image that represents the product, but vice-versa (Cova 1999).…”
Section: Modern To Post-modernmentioning
confidence: 99%
“…Alaçatı, which is preferred by many domestic and foreign windsurfers interested in the wind surf, becomes increasingly an important center with the national and international organizations of wind surf such as Surf tourism has evolved into a rapidly expanding market segment of the wider tourism industry, gaining significant attention in the academia during the previous decade (Martin and Assenov 2012). Furthermore, the surf tourism industry promises further growth with the development of more specialized services such as surf schools as well as increase of the market for surfing-related consumer brands (Moutinho, Dionısio, and Leal, 2007). The aim of this study is to analyze the current status of the windsurf schools, to learn their opinions on the development of surf tourism in the destination along with their expectations and suggestions.…”
Section: Introductionmentioning
confidence: 99%